The European Experience in Slavery, 1650-1850 edited by Rebekka von Mallinckrodt - Mallinckrodt, Rebekka von 1971- (Walter de Gruyter, 2024)
This volume documents the practice of bringing enslaved people to early modern Europe not only as a side effect of overseas colonial regimes but as a pan-European experience that even developed its own dynamics on the continent. Drawing on examples from France, Scotland, the Netherlands, Denmark, and the Holy Roman Empire, the contributors show how slavery affected both the enslaved and the enslavers' societies, changing European notions of freedom, dependence, and subjugation. At the same time, Afro-European families and cultural productions challenge the view of the Black diaspora as Europe's "other." The volume thus reveals not only the roots of present-day racism extending far back into the past, but also a common heritage yet to be discovered.